PERKEMBANGAN USAHA KERUPUK SANJAI DALAM MENGHADAPI PERSAINGAN DI BUITTINGGI - Syafnidar, Syafnidar (jurnal ekonomi, 2008)
The research is have a two goal, the firts; for to know how to development the business potato chips can be improve income and expand the market, the second; the marketing strategy that using to figth to get the market. In the research, the business potato chips get the improve and increasing income that like as omzet, product and the price. The marketing strategy will be business potato chips with marketing mix, like as product, promotion, distribution, packaging and price.